2022
DOI: 10.1503/cjs.007920
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status does not influence the presentation of patients with inguinal hernia at an urban Canadian teaching hospital

Abstract: Background: Socioeconomic status (SES) has been shown to influence the outcomes of surgical pathologies in areas with unequal access to health care. The purpose of this study was to measure the effect of SES on the urgency for inguinal hernia repair in an area with purported equitable access to health care in the context of a universal health care system. Methods: We included all adult patients who underwent surgical management of an inguinal hernia between 2012 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…This geospatial analysis did not find urbanization and poverty to be significant in comparison between coldspots and hotspots. This is supported by one prior single-institution study that found no relationship between a low socioeconomic status and presentation of an inguinal hernia [26]. In relation to the established risk factors for inguinal hernias, this study finds that age, tobacco, alcohol, and conditions with chronic cough are paradoxically correlated with regions that have reduced inguinal hernia surgeries.…”
Section: Discussionsupporting
confidence: 67%
“…This geospatial analysis did not find urbanization and poverty to be significant in comparison between coldspots and hotspots. This is supported by one prior single-institution study that found no relationship between a low socioeconomic status and presentation of an inguinal hernia [26]. In relation to the established risk factors for inguinal hernias, this study finds that age, tobacco, alcohol, and conditions with chronic cough are paradoxically correlated with regions that have reduced inguinal hernia surgeries.…”
Section: Discussionsupporting
confidence: 67%